Сharacterization of lytic activity of Phage SAvB14 on Staphylococcus aureus variant bovis - Horiuk, Yulia; Horiuk, Victor; Kukhtyn, Mykola; Tsvihun, Anatoliy; Kernychnyi, Sergiy (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The objective of this study was to investigate the intensity of phage infection caused by Phage SAvB14, which was isolated from dairy farms, depending on the initial number of Staphylococcus aureus cells in the medium. Material and methods: To evaluate the impact of the viable bacteria S. aureus var. bovis on the intensity of phage infection caused by Phage SAvB14, 1 mg of phagolysate (phage titer 105 CFU/ ml) was introduced in 9 ml of nutrient broth with an appropriate amount of daily culture of S. aureus var. bovis under study. The number of viable staphylococci was determined by total viable count/ml. Results: In this experiment, we found that the intensity of phages lytic activity was dependent on the number of sensitive bacterial cells in the volume of the culture medium. Effective phage therapy requires a high concentration of phages in the medium (inflammation foci) for rapid contact of the virus with bacteria. Conclusion: When developing a phage drug to treat subclinical mastitis, it is necessary to increase the phage titer in the drug or its dosage compared to the clinical form, as there is a lower probability of phage contact with a susceptible microbial cell. Besides, at a high concentration of bacteria, there is a gradual decrease in nutrients in the medium, resulting in phages going back to the condition of lysogeny. J. Adv. Vet. Anim. Res., 7(3): 509-513, Sep 2020 http://doi.org/10.5455/javar.2020.g447